The Effect of Cost Determination in the Provision of Halal Certificates on Traded Products in Makassar City - Azzah Azimah Assagaf; Juajir Sumardi; Winner Sitorus (UIN Sunan Gunung Djati, 2022)
In terms of food or goods and their use, Islam commands its followers to eat and use good, holy, and clean ingredients. Allah Subhanahu Wa Ta'ala says which means: